Adverse Pregnancy Outcomes Among Khat Chewing Pregnant Mothers in Meru County, Kenya. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Khat (Catha edulis) is a green leafy plant containing psychoactive alkaloids, such as cathine and cathinone. Khat use in pregnancy affects maternal and fetal well-being.Objective: This study aimed to determine the risk of adverse pregnancy outcomes among pregnant women who chew khat compared with pregnant women who do not chew khat in Meru County in 2023.Methods: A retrospective cohort study was employed at the Meru Teaching and Referral Hospital and Nyambene Level 4 Hospital that compared immediate postpartum mothers who chewed khat during pregnancy (exposed, n=150) and those who did not chew khat during pregnancy (unexposed, n=300). Data on khat chewing during pregnancy and various maternal, fetal, and early neonatal outcomes were collected using a questionnaire. Data were summarized as means, frequency, and percentages and com  pared using the Students t-test, Pearson’s Chi-square, and Fischer’s exact test. All statistical tests were considered significant if the p